Enhanced Field Ionization Enabled by Metal Induced Surface States on Semiconductor Nanotips. (5th December 2013) - Karaagac, H.; Islam, M. Saif
<x xml:space="preserve">Abstract</x> Recent progress in the realization of material structures with quantum confinement and high surface to volume ratio in nanoscale interwoven metal and semiconductor building blocks offers a strong potential to build highly functional nanodevices. Ultra‐sharp tips with distinct material dependent properties of metal and semiconductor exhibit important functionalities in devices including gas ionization sensors, field emission devices, and ion‐mobility spectrometry. Herein, a dramatically enhanced field ionization process and a device based on charged particle beams for which the geometrical and surface properties of the constituent semiconductor nanotips are engineered with controlled introduction of metallic impurities to realize close to three orders of magnitude reduction in the ionization electric‐field strength are described. Experimentally observed low voltage field ionization phenomenon is explained using the geometrical field enhancement, surface states induced by controlled introduction of metallic impurities, and polarizabilities of gas particles at the nanotips. The nanotips are employed to design field ionization gas sensors whose nanoscale pristine semiconductor tips are controllably decorated with atomic metal impurities to boost the electron tunneling properties under extremely low bias voltages. These devices also outperform their solid‐state macroscopic counterparts in terms of simplicity of their construction and higher selectivity.